2005
DOI: 10.1071/wf05039
|View full text |Cite
|
Sign up to set email alerts
|

Microbial recolonization and chemical changes in a soil heated at different temperatures

Abstract: Samples of a Mediterranean forest soil were exposed in a muffle furnace to seven temperatures (100–700°C) for 15 min to simulate different fire intensities. Heated soils were incubated for 100 days after re-inoculation with fresh unheated soil. Immediately after heating, the extractable organic C increased with the heating temperature, reaching a maximum at 400°C. This increase in extractable organic C and nutrients in soils heated below 400°C allowed a rapid recolonization of bacteria, increasing the basal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 57 publications
4
48
0
Order By: Relevance
“…It is, therefore, surprising that this study appears to be the first to consider post-fire recolonization of plant-associated fungi. Investigations into the effect of fire on soil microbial biomass in Mediterranean regions (Dumontet et al, 1996) have revealed that fungi are more susceptible to fire and re-establish less easily than bacteria (Bárcenas-Moreno et al, 2011;Guerrero et al, 2005). The niche space availability and elimination of competition provided by fire, however, apparently facilitates rapid re-establishment.…”
Section: Recolonization Of Recently Burnt Areasmentioning
confidence: 99%
“…It is, therefore, surprising that this study appears to be the first to consider post-fire recolonization of plant-associated fungi. Investigations into the effect of fire on soil microbial biomass in Mediterranean regions (Dumontet et al, 1996) have revealed that fungi are more susceptible to fire and re-establish less easily than bacteria (Bárcenas-Moreno et al, 2011;Guerrero et al, 2005). The niche space availability and elimination of competition provided by fire, however, apparently facilitates rapid re-establishment.…”
Section: Recolonization Of Recently Burnt Areasmentioning
confidence: 99%
“…Different groups of microorganisms show different strategies against disturbances. Fungi, for example, often show greater resistance than bacteria (Dunn et al, 1985), although bacteria can recover faster (Guerrero et al, 2000;Guerrero et al, 2005;Bárcenas-Moreno and Baath, 2009;Ponder et al, 2009;Bárcenas-Moreno et al, 2011). However, if fire intensity is sufficiently high, soil may become partially sterilized (Pietikäinen and Fritze, 1995).…”
Section: Effects On Soil Biotic Componentsmentioning
confidence: 99%
“…Plant-available ammonium and nitrate can increase concomitantly with temperature and duration until they begin to volatilize [4,5], which most likely occurs on sites containing black-colored soils (PFI categories 2.1-2.3 and 3.1-3.3). As organic carbon is volatilized, concentrations of inorganic compounds such as potassium increase, although little change occurs with calcium [93]. Thus, in PFI categories 3.3 and 3.4 or 4.3 and 4.4 with gray or orange colored soils [6,47] several inorganic elements would be abundant.…”
Section: Relating the Pfi To Post-fire Soil Nutrientsmentioning
confidence: 99%
“…If gray ash is abundant and there is little to no surface organic layer remaining, a large portion of the total nitrogen may be absent (PFI category 4.3) [4]. However, if there is an abundance of surface organic material (PFI categories 1.0 and 2.0), and no gray-or orange-colored soils, [6,45,46], temperatures were insufficient to volatilize all the nitrogen [93]. Plant-available ammonium and nitrate can increase concomitantly with temperature and duration until they begin to volatilize [4,5], which most likely occurs on sites containing black-colored soils (PFI categories 2.1-2.3 and 3.1-3.3).…”
Section: Relating the Pfi To Post-fire Soil Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation